Respostas

2013-05-12T19:58:52-03:00

Sabe-se que   cos² x + sen² x  = 1

 

                           como  senx = √3/4

 

              

              vem :    cos² x  = 1 - sen² x

 

             Substituindo temos :       cos² x  =  1 - ( √3/4 )²

 

                              temos que :      cos² x  =  1 - 3/16

 

 

                                     assim:     cos² x = (16-3)/16

 

     

                                     logo :        cos² x  = 13/16

 

             

                                      temos que :    cos x =  √13/√16

 

                                        assi:            cos x =   √13/ 4

 

 

                                         tag x =  sen x  / cos x

 

 

                                         tag x =   √3/4  /   √13/4

 

 

 

                                resposta :       tag x  =  √39 / 13

1 5 1
2013-05-12T21:01:56-03:00

cos² x +sen² x =1
(V3/2)²+sen² x = 1
sen² x = 1-3/4
sen² x = 1/4
sen x = +- 1/2 copmo o anguylo pertençe ao 1º quadrante logo sen x = 1/2
tg x = sen x /cos x
tg x= (1/2)/ (V3/2) = > 1/2 x 2/V3 => 1/V3 = V3/3

1 4 1